Estudos por Ressonância Magnética Nuclear das Estruturas dos Peptídeos Homotarsinina e LyeTx I mnK Ac e do Alinhamento Magnético de Bicelas Fosfolipídicas - Breno Pires de Andrade Barbosa (2016)
The study of antibacterial peptides has shown a great potential to substitute a great number of different antibiotics in the fight against super bacteria. Several studies show that the antibacterial activity is intrinsically linked to the conformation adopted by these peptides when in contact with bacteria phospholipid membranes. This work is divided in three different chapters. The necessity of magnetically oriented biomimetic media for this study brought a new challenge in relation to the orientation of bicelles. This lead to the search for new data about the time dependence orientation of bicelles exposed to magnetic fields of different magnitudes. The second chapter covers the topological study of the homodimeric peptide homotarsinin, originally isolated from the skin secretion of the tree frog Phyllomedusa tarsius, when bound to media that mimics bacterial cellular membranes. These topological studies were performed in membrane environments by nuclear magnetic resonance and they look to elucidate the relative orientation adopted by the two chains within the homodimer structure. The last part of this work shows the results obtained by nuclear magnetic resonance and computational calculations about the structure of the antibacterial peptide LyeTx I mnK Ac, which was obtained by chemical modifications of the wild type peptide LyeTx I, originally isolated from the venom of the arachnid Lycosa erythrognatha.